Arbuscular mycorrhizal fungi enhance mineralisation of organic phosphorus by carrying bacteria along their extraradical hyphae - Jiang, Feiyan; Zhang, Lin; Zhou, Jiachao; George, Timothy S.; Feng, Gu (The New phytologist, 2021)
• Arbuscular mycorrhizal (AM) fungi gain access to nutrient patches outside the rhizosphere by producing an extensive network of fine hyphae. Here, we focused on establishing the mechanism by which AM fungal hyphae reach discrete organic patches with a cohort of functional bacteria transported in a biofilm on their surface. • We investigated the mechanisms and impact of the translocation of phosphate solubilising bacteria (PSB) along AM fungal hyphae in bespoke microcosms. An in vitro culture experiment was also conducted to determine the direct impact of hyphal exudates of AM fungi upon the growth of PSB. • The extraradical hyphae of AM fungi can transport PSB to organic phosphorus (P) patches and enhance organic P mineralisation both under in vitro culture and soil conditions. Bacteria move in a thick water film formed around fungal hyphae. However, the bacteria cannot be transferred to the organic P patch without an energy source in the form of hyphal exudates. • Our results could be harnessed to better manage plant–microbe interactions and improve the ability of biological inocula involving AM fungi and bacteria to enhance the sustainability of agricultural crops in P limited conditions.